Problems of calculation of heat transfer crisis in fuel assembles of water cooled reactors - G. I. Sharaevsky; N. М. Fialko; L. B. Zimin; I. G. Sharaevsky (Ядерна фізика та енергетика)
Current problem of the ensuring reliability of the results of mathematical computer simulation of the operational modes of water-cooled nuclear reactors is considered in this article. An analysis of the adequacy of computer software systems, which are designed to calculate the main parameters of the safety of WWR reactors is performed The main focus is devoted to the methodology for determining the technological security of the active zones reactor plants settings, using the modern thermal-hydraulic codes. This calculation is based on determining the thermal-hydraulic parameters of the flow of coolant in the fuel rod assembled elements. The results of the comparison of experiments performed to determine the distribution of the main thermal-hydraulic flow parameters of subchannels of fuel rod assembled elements with the data for calculating these parameters on the basis of computer codes are introduced. Particular attention is paid to the analysis of experimental and calculated data, by the definition of burnout in the fuel rods assembled elements. The basic directions of perfection of the modern thermal-hydraulic codes to improve the reliability of determination of thermophysical parameters of safety for the water-cooled nuclear reactors were considered.